Imaging of the foot and ankle - Berquist, Thomas H. (Thomas Henry), 1945-; ebrary, Inc. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Revised and updated for its Third Edition, this highly acclaimed volume is a definitive guide to the clinical imaging of foot and ankle disorders. The title of this edition has changed from Radiology of the Foot and Ankle to Imaging of the Foot and Ankle to reflect a greater emphasis on multimodality imaging approaches to solve diagnostic challenges, specifically the increased use of ultrasound, MR imaging, CT, and diagnostic interventional techniques. The book features increased coverage of ultrasound, PET, and the diabetic foot and upgraded MR and CT images. New syndromes such as impingement have been added to the chapter on soft tissue trauma and overuse. The fractures and dislocations chapter includes OTA classifications and additional MR and CT scans of complications. Other highlights include up-to-date information on new fixation devices and prostheses and state-of-the-art interventional and vascular techniques including use of MRA. This book provides a comprehensive reference for radiologists, radiologists in training, and clinicians who treat foot and ankle disorders including podiatrists, orthopaedic surgeons, rheumatologists, and emergency room physicians"--Provided by publisher.
(Publisher-supplied data) Anatomy, Normal Variants and Basic Biomechanics / Thomas H. Berquist -- Diagnostic Techniques / Thomas H. Berquist -- Soft Tissue Trauma and Overuse Syndromes / Thomas H. Berquist -- Fracture/Dislocations / Thomas H. Berquist -- Arthritis / Thomas H. Berquist and Laura W. Bancroft -- Bone and Soft Tissue Tumors and Tumor-Like Conditions / Thomas H. Berquist and Mark J. Kransdorf -- Infection / Thomas H. Berquist -- Bone and Soft Tissue Ischemia / Thomas H. Berquist and Anthony B. Adelson -- Pediatric Foot and Ankle Disorders / Thomas H. Berquist, Laura W. Bancroft and Debbie J. Merinbaum -- Reconstructive Procedures: Preoperative and Postoperative Imaging / Thomas H. Berquist and Joseph L. Whalen -- Miscellaneous Conditions / Thomas H. Berquist.
Rev. edition of: Radiology of the foot and ankle / editor, Thomas H. Berquist. 2nd edition c2000.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2014. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Foot -- Imaging; Ankle -- Imaging; Foot -- Diseases -- Diagnosis; Ankle -- Diseases -- Diagnosis; Electronic books